KAPASITAS SERAPAN DAN ENERGI IKAT PADA BIOSORSPSI ION MANGAN(II) OLEH BIOMASSA Saccharomyces cerevisiae TERIMOBILISASI PADA CAMPURAN SILIKA GEL DAN ZEOLIT - Jasmidi Jasmidi; Rahmat Nauli (Pascasarjana Universitas Negeri Medan, 2014)
Abstract. This research aims to study the uptake capacity and binding energy in ion biosorption of manganese(II) by biomass S. cerevisiae immobilized on silica gel and zeolite mixture. As for the method is performed by varying the initial concentration of manganese(II) in solution were contacted with biomass S. cerevisiae immobilized on silica gel and zeolite. To determine the concentration of manganese(II) in the solution used visible spectrophotometric method, using complexing formaldoksim. amount of manganese ions(II) adsorbed by the immobilized biomass was determined by calculating the difference between the concentration of manganese(II) contained in the solution before and after contacted. The results showed that the absorption of manganese(II) increased linearly as a function of concentration up to 50 mg/L, sorption capacity calculations obtained using Langmuir isotherm equation was 10.989 mg/g or 2,0 x 10-4 mol/g dry weight biomass S. cerevisiae immobilized. Binding energy value between biomass S. cerevisiae immobilized with manganese ions (II) is 30.69 kJ/mol. Thus the interaction is a chemical interaction Key words : Absorption capacity, binding energy, S. cerevisiae, immobilization.